Compensatory intestinal antibody response against pro-inflammatory microbiota after bariatric surgery. (31st December 2022) - Scheithauer, Torsten P.M.; Davids, Mark; Winkelmeijer, Maaike; Verdoes, Xanthe; Aydin, Ömrüm; de Brauw, Maurits; van de Laar, Arnold; Meijnikman, Abraham S.; Gerdes, Victor E.A.; van Raalte, Daniël; Herrema, Hilde; Nieuwdorp, Max
ABSTRACT: Obesity and type 2 diabetes (T2D) are growing burdens for individuals and the health-care system. Bariatric surgery is an efficient, but drastic treatment to reduce body weight, normalize glucose values, and reduce low-grade inflammation. The gut microbiome, which is in part controlled by intestinal antibodies, such as IgA, is involved in the development of both conditions. Knowledge of the effect of bariatric surgery on systemic and intestinal antibody response is limited. Here, we determined the fecal antibody and gut microbiome response in 40 T2D and non-diabetic (ND) obese individuals that underwent bariatric surgery (N = 40). Body weight, fasting glucose concentrations and inflammatory parameters decreased after bariatric surgery, whereas pro-inflammatory bacterial species such as lipopolysaccharide (LPS), and flagellin increased in the feces. Simultaneously, concentrations of LPS- and flagellin-specific intestinal IgA levels increased with the majority of pro-inflammatory bacteria coated with IgA after surgery. Finally, serum antibodies decreased in both groups, along with a lower inflammatory tone. We conclude that intestinal rearrangement by bariatric surgery leads to expansion of typical pro-inflammatory bacteria, which may be compensated by an improved antibody response. Although further evidence and mechanistic insights are needed, we postulate that this apparent compensatory antibody response might help to reduce systemic inflammation by neutralizing intestinal immunogenic components and thereby enhance intestinal barrier function after bariatric surgery.